Policies for the sustainable development of biofuels in the Pan American region: a review and synthesis of five countries - Solomon, Barry D. (2015)
Rapid growth of biofuel production in the United States and Brazil over the past decade has increased interest in replicating this success in other nations of the Pan American region. However, the continued use of food-based feedstock such as maize is widely seen as unsustainable and is in some cases linked to deforestation and increased greenhouse gas emissions, raising further doubts about long-term sustainability. As a result, many nations are exploring the production and use of cellulosic feedstock, though progress has been extremely slow. In this paper, we will review the North–South axis of biofuel production in the Pan American region and its linkage with the agricultural sectors in five countries. Focus will be given to biofuel policy goals, their results to date, and consideration of sustainability criteria and certification of producers. Policy goals, results, and sustainability will be highlighted for the main biofuel policies that have been enacted at the national level. Geographic focus will be given to the two largest producers—the United States and Brazil; two smaller emerging producers—Argentina and Canada; and one stalled program—Mexico. However, several additional countries in the region are either producing or planning to produce biofuels. We will also review alternative international governance schemes for biofuel sustainability that have been recently developed, and whether the biofuel programs are being managed to achieve improved environmental quality and sustainable development.